Sleep pattern, weight gain status and body composition of women with gestational diabetes mellitus (gdm) and healthy pregnancy - Roslan, Aimi Yuhanis Mohd (Universiti Sains Malaysia, 2016)
Pregnancy is the most important and interesting period in women. During the pregnancy period, there were some physical, psychological and biological changes that experienced by the pregnant women. The objective of this study was to determine the association between sleep pattern and nutritional status (weight gain status and body composition measurement) among pregnant women at HUSM. The validated Pittsburgh Sleep Quality Index Malay Version (PSQI-M) questionnaires were distributed to pregnant women aged 20 to 40 years old within their second to third trimester at Obstetrics and Gynecology Clinic, Antenatal Ward Akik and Baiduri at HUSM. The questionnaire measure seven domains; subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbance, use of sleep medication, and daytime dysfunction over the last month. The Global PSQI-M score was summed up from all the seven domains and the score range are between O to 21. The respondents with Global PSQI-M score less than or equal to 5 are considered having good sleep quality and respondents with Global PSQI-M score more than 5 are considered having poor sleep quality. Anthropometry indicators include pre-pregnancy weight, prepregnancy BMI, weight and height during pregnancy, BMI during pregnancy and body composition measurements. Body composition was measured using body composition analyzer (T ANITA SC-330GS) and this instrument gives reading of weight, total fat mass, fat mass percentage, fat-free mass, total body water, body water percentage and BMI based on the bioelectrical impedance analysis technology. A total 99 respondents completed the study. Sixty respondents were in healthy pregnancy and 39 respondents were GDM during pregnancy. There was no significant association between sleep pattern and weight gain status (p=0.782). However, there was a significant association between sleep pattern and visceral fat rating (p=0.037) and there was a significant correlation between sleep pattern and body fat percentage (p=0.011). Thus, this study showed that visceral fat rating and body fat percentage of pregnant women have a strong link with sleep pattern of them than weight gain status.